A starch luminescent material and its preparation method and application
By oxidative modification of starch and covalent modification of organic luminescent small molecules, starch luminescent materials with full-band luminescent properties were prepared, which solved the difficulties in experimental reproducibility and versatility design of existing materials, and achieved stable full-band luminescent performance and wide applicability.
Patent Information
- Application Number
- CN202311680860.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-08
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2043-12-08
AI Technical Summary
The existing starch luminescent materials have poor experimental reproducibility during the preparation process, and the material design concept is difficult to target versatility, and there are problems of non-biodegradation and potential toxicity, making it difficult to achieve full-band luminescence.
By oxidative modification of the starch, the carboxyl group is activated and the organic luminescent small molecules modified by amino group are covalently reacted through amide bonds to stably modify the organic luminescent small molecules on the starch molecules, and a starch luminescent material with full-band luminescent properties is prepared.
The full-band luminescence of starch luminescent materials is achieved, the original particle structure and multi-scale structure of starch are maintained, and it is suitable for oxidized starch from various sources, and maintains stable luminescence performance under different states (grains or gels), which is suitable for a variety of application environments.
Smart Images

Figure CN117903327B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of starch functionalized materials, and in particular to a method for preparing a luminescent material based on oxidized starch and application thereof. Background Art
[0002] Fluorescence refers to a cold luminescence phenomenon of photoluminescence (de Silva et al., 1997). When a certain substance at room temperature is irradiated by incident light of a certain wavelength (usually ultraviolet light or X-rays), it absorbs light energy and transitions from the ground state to the excited state, and then immediately returns to the ground state, while emitting an outgoing light with a longer wavelength than the incident light, usually in the visible light band (Wu, Sedgwick, Gunnlaugsson, Akkaya, Yoon, & James, 2017). In the context of the increasing depletion of petrochemical and mineral energy, organic and inorganic fluorescent materials derived from petrochemicals and minerals also face problems such as non-renewable, high cost and high environmental load. In addition, the potential toxicity and poor biocompatibility of traditional inorganic quantum dots and organic luminescent small molecules further limit their application. Due to the renewability and low cost of biomass resources, the progress of biomass luminescent materials and their multifunctional applications has attracted more and more attention in the past decade (Irimia-Vladu, 2014). Starch is one of the largest naturally occurring high-molecular carbohydrates in nature. It is distributed in the plant kingdom and is the main source of energy for people. It is also an important industrial raw material and is widely used in papermaking, textiles, medicine, food and fermentation.
[0003] Natural starch and modified starch have been widely used in various material applications, accounting for one-fifth of all biomass materials (Klemm, Heublein, Fink, & Bohn, 2005). Starch itself is colorless and odorless. It has good biodegradability and compatibility, reusability, hydrophilicity, thermal stability and strong adsorption capacity. In addition, starch contains many hydroxyl groups, so it can be modified into starch esters, ethers and other starch derivatives through simple chemical reactions (Fu, Jiang, & Yao, 2022), and then further prepared into starch functional materials. In the field of starch biomass fluorescence, the main research is to prepare organic aggregated luminescent or carbon-based materials with fluorescence emission functions by means of hydrolysis extraction, hydrothermal carbonization or molecular assembly. Among them, the luminescence mechanism and formation process of starch-based carbon quantum dots are still unclear. This preparation method not only has poor experimental reproducibility, but also makes it difficult to design multifunctional starch fluorescent materials based on material design concepts. It also has factors such as non-biodegradability and potential toxicity to organisms.
[0004] Different from the above-mentioned inorganic carbon quantum dot materials, organic luminescent starch materials have been considered as a research hotspot for starch luminescent materials in recent years due to their good designability, ideal biodegradability and biocompatibility, and easy manufacturing. As mentioned earlier, starch contains a large number of hydroxyl functional groups, which can be modified into other groups such as carboxyl and amino groups through chemical modification methods, and then connected to organic fluorescent small molecules to give it fluorescence and other properties. At present, there are few studies on maintaining the structure of starch itself and achieving luminescence by modifying small molecule fluorescent groups, especially starch materials with full-band luminescence. Therefore, based on the above research, it is of great significance to select suitable starch raw materials and combine fluorescent groups with different luminescence bands to develop starch luminescent materials with full-band. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a starch luminescent material and its application. The present invention can target starches of various sources and perform oxidation modification on them in different ways, and can endow the starch material with full-band luminescent properties by chemically modifying organic luminescent small molecules.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] A method for preparing a starch luminescent material comprises: activating the carboxyl groups of oxidized starch, stably modifying the organic luminescent molecules on starch molecules based on the amide bond covalent reaction between the carboxyl groups of the oxidized starch and the amino groups of amino-modified organic luminescent molecules, and preparing the starch luminescent material.
[0008] Preferably, the method comprises the following steps: fully dispersing the oxidized starch in water, adjusting the pH to 4-6, adding N-hydroxysuccinimide (NHS) and 1-ethyl-(3-dimethylaminopropyl)carbodiimide (EDC) to activate the carboxyl group, and then slowly adding an amino-modified organic luminescent small molecule solution, stirring the reaction in the dark, washing with water, centrifuging and filtering, and drying to obtain a starch luminescent material.
[0009] Preferably, the starch luminescent material is gelatinized to obtain a starch luminescent hydrogel.
[0010] Preferably, the mass concentration of the oxidized starch is 0.01-2 g / mL; the NHS accounts for 1-50% of the dry weight of the oxidized starch; and the EDC accounts for 1-50% of the dry weight of the oxidized starch.
[0011] Preferably, the mass concentration of the oxidized starch is 0.01-0.05 g / mL; the NHS accounts for 20-40% of the dry weight of the oxidized starch; and the EDC accounts for 20-40% of the dry weight of the oxidized starch.
[0012] Preferably, the amino-modified organic light-emitting small molecules are one or more than two light emitting in the red to blue light band.
[0013] Preferably, the amino-modified organic luminescent small molecule accounts for 1-10% of the dry weight of the oxidized starch; the amino-modified organic luminescent small molecule is aniline, naphthylamine, amino-carbazole, amino-thiazole, amino-methyl orange.
[0014] Preferably, the concentration of the amino-modified organic luminescent small molecule solution is 0.5-10 mg / mL.
[0015] Preferably, the amino-modified organic luminescent small molecule solution is an organic solvent miscible with water, such as DMSO and DMF.
[0016] Preferably, the oxidized starch is obtained by oxidizing starch using an oxidant; the starch is one or more of corn starch, cassava starch, and potato starch; the oxidant is one or more of sodium hypochlorite, laccase, and 2,2,6,6-tetramethylpiperidinyl oxide (TEMPO).
[0017] Preferably, the reaction temperature is 0-50°C, the reaction time is 4-24 hours, and the drying temperature is 35-55°C.
[0018] The starch luminescent material prepared by the above method is used in information sensing, anti-counterfeiting identification, and biomedicine.
[0019] Compared with the prior art, the present invention has the following outstanding advantages:
[0020] 1. The present invention is based on the covalent reaction of amide bonds between the carboxyl groups of oxidized starch and the amino groups of organic light-emitting molecules, and successfully stably modifies the organic light-emitting molecules on the starch molecules. Moreover, the reaction is a solid-liquid phase reaction, which can maintain the original granular structure of the starch and the original multi-scale structure.
[0021] 2. The present invention has wide applicability and is applicable to oxidized starch prepared from various sources and different ways. At the same time, as long as the organic luminescent small molecule has a reactive amino group, it can react, and starch luminescent materials with different luminescent bands can be prepared according to specific needs. Whether in a granular state or after gelatinization into a gel state, it can still maintain stable luminescent properties, and can better meet the needs of different application environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the technical roadmap for Example 1.
[0023] Figure 2 ] are infrared spectra of oxidized starch OMS and OMS-NA of Example 1.
[0024] Figure 3 : SEM images of the embodiments; A is oxidized starch OMS, C is its enlarged view; B is OMS-NA of Example 1, D is its enlarged view.
[0025] Figure 4 It is the ultraviolet absorption spectrum of Example 1 and 2.
[0026] Figure 5 The fluorescence emission spectra of Examples 1 and 2 are shown in FIG.
[0027] Figure 6 a, b, and c are the luminescent images of starch particles in Examples 1, 6, and 7, respectively.
[0028] Figure 7 a, b, and c are the luminescence images of the starch gel of oxidized starch OMS, Example 6, and Example 4, respectively.
[0029] Figure 8 a and b are luminescence images of oxidized starch OMS and starch gel of Example 1 respectively.
[0030] Fig. 9 This is the electron cloud distribution and ESP electrostatic potential distribution of quantum chemistry simulation. DETAILED DESCRIPTION
[0031] The present invention is further described in detail below in conjunction with examples and drawings, but the embodiments of the present invention are not limited thereto.
[0032] Example 1
[0033] Step 1: Accurately weigh 5g of commercial corn starch (dry basis) in 100mL of 0.1M phosphate citrate buffer (pH=5), add TEMPO (15% w / w based on starch dry weight) and laccase (6% w / w based on starch dry weight) at room temperature, and stir at room temperature for 12 hours at a stirring rate of 200rpm. After the reaction is completed, the reaction product is filtered through a Buchner funnel and washed 5 times with 500mL of deionized water until the laccase (laccase is food grade, from Sigma-Aldrich, USA) and TEMPO in the product are completely removed, and then the filter cake is dispersed and placed in an oven for drying (45°C), and finally ground and sieved for use to obtain C6-directed modified oxidized starch OMS.
[0034] Step 2: Disperse oxidized starch (1g) in deionized water (100ml), adjust the pH to 5 with HCl (0.1mol / L) and ultrasonically disperse for 30 minutes. Then, add NHS (0.3g, 2.6mmol) to the reaction process, stir for 30min, then add EDC (0.3g, 1.7mmol) and stir for 30min. Then, slowly drop naphthylamine (0.05g, 1.3mmol) dissolved in N, N-dimethylformamide (DMF) under nitrogen. The reaction was carried out at room temperature for 24 hours. After the reaction was completed, precipitate with excess tetrahydrofuran (THF), filter and wash repeatedly with ethanol until the filtrate was clear. After the filtration was completed, the starch was transferred to an oven to dry overnight at a drying temperature of 45°C. The starch luminescent material OMS-NA was obtained.
[0035] Example 2
[0036] The difference between this embodiment and embodiment 1 is that in step 1, in the preparation of oxidized corn starch, commercially available sodium hypochlorite oxidized starch is selected to prepare the starch luminescent material OS-NA.
[0037] Example 3
[0038] The difference between this embodiment and embodiment 1 is that the organic solvent for dissolving naphthylamine is replaced with DMSO to prepare the starch hydrogel OMS-NA1.
[0039] Example 4
[0040] The difference between this embodiment and embodiment 1 is that the organic light-emitting small molecule is replaced with aniline to obtain the starch light-emitting material OMS-Na.
[0041] Example 5
[0042] The difference between this embodiment and embodiment 1 is that the organic light-emitting small molecule is replaced with amino-carbazole to obtain the starch light-emitting material OMS-Cz.
[0043] Example 6
[0044] The difference between this embodiment and embodiment 1 is that the organic light-emitting small molecule is replaced with amino-thiazole to obtain the starch light-emitting material OMS-SZ.
[0045] Example 7
[0046] The difference between this embodiment and embodiment 1 is that the organic light-emitting small molecule is replaced with amino-methyl orange to obtain the starch light-emitting material OMS-CH.
[0047] Example 8
[0048] The difference between this embodiment and embodiment 1 is that the amount of the organic light-emitting small molecule added is 0.1 g, and the starch light-emitting material OMS-NA2 is obtained.
[0049] Example 9
[0050] The difference between this embodiment and embodiment 1 is that 0.5 g of NHS and EDC are subsequently added to obtain the starch luminescent material OMS-NA3.
[0051] The present invention conducts surface morphology and photophysical property measurement tests on the above-mentioned embodiments, as follows:
[0052] 1. Morphology and structure:
[0053] The SEM test method is to use conductive glue to stick the prepared starch luminescent particles to the sample stage. First, stick a layer of conductive double-sided tape on the surface of the sample stage, sprinkle a small amount of powder sample on it, flick the sample stage to make the sample evenly spread, press it lightly to make it stick to the glue surface, and blow away the excess powder with an ear bulb. Then place the sample stage in an ion sputtering coater for gold plating for 300s, take it out and put it into the SEM sample chamber. Test at a voltage of 10kV, the distance between the sample and the probe is about 9mm, and select a representative area for photography at an appropriate magnification.
[0054] Experimental results:
[0055] like Figure 2 As shown, compared with the oxidized starch OMS, the OMS-NA spectrum in Example 1 shows a peak at 1654 cm -1 The infrared absorption peak at is the characteristic absorption peak of CO-NH amide bond I region, indicating that after the reaction, NA is successfully covalently modified on the carboxyl group of oxidized starch with amide bond.
[0056] from Figure 3 It can be observed that the corn starch particles are irregular polygonal shapes, most of the particle sizes are distributed in the range of 5-13 μm, and a very small number of particles are distributed in the range of 0.3-3 μm. Compared with the corn starch particles, the morphology of the oxidized starch particles modified in Example 1 basically maintains the original morphology without obvious changes, indicating that the oxidation reaction and the subsequent amidation reaction are relatively mild, so that starch particles with a complete morphology structure can be obtained.
[0057] from Figure 4 As shown, the ultraviolet absorption of the starch luminescent material in Example 1 and Example 2 is slightly red-shifted compared to the original organic small molecule luminescent material, but still maintains a similar absorption band, indicating that the absorption band of the small molecule luminescent material is not affected after the amide bond modification. Figure 5As shown, the fluorescence emission of the starch luminescent material in Example 1 and Example 2 is slightly red-shifted compared to the original organic small molecule luminescent material, but still remains in the blue light region, indicating that after amide bond modification, the emission band of the starch luminescent material is consistent with the original organic small molecule luminescent material. And the starch luminescent material prepared by oxidized starch obtained in different ways has no significant effect on its subsequent photophysical properties, indicating the versatility of this method.
[0058] Table 1 Maximum emission wavelengths of Examples 1-9 of the present invention in particle and gel states
[0059]
[0060] As can be seen from Table 1, the starch luminescent materials prepared from oxidized starch obtained in different ways have no significant effect on their subsequent photophysical properties; and different solvents have no significant effect on the subsequent photophysical properties of the prepared starch luminescent materials, indicating the versatility and universality of this method. At the same time, by changing the organic small molecule luminescent groups with different emission wavelengths, starch luminescent materials with different emission bands (from blue light to red light) can be obtained in a directionally manner. Moreover, after the starch granules are gelatinized, although the emission wavelength of the resulting gel is slightly red-shifted, it still maintains a similar position, indicating the universality and superiority of this method. Figure 6 and Figure 7 It can be seen that starch luminescent materials can obtain similar luminescent properties regardless of whether they are in particle form or gel state, and can meet the needs of different applications.
[0061] Table 2 Luminescence lifetime of Examples 1-9 of the present invention in gel state
[0062]
[0063]
[0064] As shown in Table 2, the starch luminescent materials prepared by oxidized starch obtained in different ways have no significant effect on their subsequent luminescence; and different solvents and different material ratios have no significant effect on the subsequent luminescence lifetime of the prepared starch luminescent materials, indicating the versatility and universality of this method. At the same time, by changing the organic small molecule luminescent groups with different emission wavelengths, their luminescence lifetimes are basically maintained in the nanosecond range.
[0065] Depend on Fig. 9 It can be seen that the quantum simulation results show that after the photosensitizer is modified, the carbonyl π electrons in the amide bond will produce n-π* transitions with the n electrons in the oxygen and nitrogen atoms, and then the electron delocalization effect will occur. The increase in the electron delocalization effect reduces the band gap of the molecule, resulting in a red shift in the emission wavelength. Therefore, although the overall electron cloud of the modified starch luminescent material moves slightly toward the glucose unit, the luminescence energy level and position remain basically unchanged compared with the original photosensitizer.
[0066] The above contents are further detailed descriptions of the present invention in combination with specific preferred embodiments, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art of the present invention, several equivalent substitutions or obvious variations can be made without departing from the concept of the present invention, and the performance or use is the same, which should be regarded as belonging to the protection scope of the present invention.
Claims
1. A method for preparing a starch luminescent material, characterized in that: The oxidized starch is carboxyl activated, and based on the amide bond covalent reaction between the carboxyl group of the oxidized starch and the amino group of the amino-modified organic luminescent small molecule, the organic luminescent molecule is stably modified on the starch molecule to prepare the starch luminescent material.
2. The preparation method according to claim 1, characterized in that: The following steps are involved: The oxidized starch was fully dispersed in water, the pH was adjusted to 4-6, NHS and EDC were added for carboxyl activation, and then the amino-modified organic luminescent small molecule solution was slowly added. After fully stirring the reaction in the dark, the starch luminescent material was washed with water, centrifuged and dried.
3. The preparation method according to claim 2, characterized in that: The starch luminescent material is gelatinized to obtain a starch luminescent hydrogel.
4. The preparation method according to claim 2 or 3, characterized in that: The mass concentration of the oxidized starch is 0.01-2 g / mL; the NHS accounts for 1-50% of the dry weight of the oxidized starch; and the EDC accounts for 1-50% of the dry weight of the oxidized starch.
5. The preparation method according to claim 4, characterized in that: The mass concentration of the oxidized starch is 0.01-0.05 g / mL; the NHS accounts for 20-40% of the dry weight of the oxidized starch; and the EDC accounts for 20-40% of the dry weight of the oxidized starch.
6. The preparation method according to claim 5, characterized in that: The amino-modified organic luminescent small molecule accounts for 1-10% of the dry weight of the oxidized starch; the concentration of the amino-modified organic luminescent small molecule solution is 0.5-10 mg / mL; the amino-modified organic luminescent small molecule is aniline, naphthylamine, amino-carbazole, amino-thiazole, and amino-methyl orange.
7. The preparation method according to claim 6, characterized in that: The oxidized starch is obtained by oxidizing starch with an oxidant; the starch is one or more of corn starch, cassava starch, and potato starch; the oxidant is one or more of sodium hypochlorite, laccase, and 2,2,6,6-tetramethylpiperidinyl oxide.
8. The preparation method according to claim 7, characterized in that: The reaction temperature is 0-50°C, the reaction time is 4-24 hours, and the drying temperature is 35-55°C.
9. The starch luminescent material obtained by the method according to any one of claims 1 to 8.
10. Use of the starch luminescent material according to claim 9 in information sensing and anti-counterfeiting identification.
Citation Information
Patent Citations
Fluorescent starch nanocrystal and preparation method and application thereof
CN105061608A